2021
DOI: 10.1111/1440-1703.12262
|View full text |Cite
|
Sign up to set email alerts
|

Relative importance of host‐dependent versus physical environmental characteristics affecting the distribution of an ectoparasitic copepod infecting the mouth cavity of stream salmonid

Abstract: Understanding parasite distributional patterns is fundamental for elucidating host-parasite relationships. The genus Salmincola is an ectoparasitic copepod group specifically infecting freshwater salmonids. Considering their strong association with their hosts, we can predict that the distribution and prevalence (analogs to abundance) of Salmincola reflect host salmonids. An alternative hypothesis is that their distribution will be strongly affected by environmental factors like stream drift because they have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…edwardsii may be dependent on host density, as has been noted for other Salvelinus fishes (Hasegawa & Koizumi, 2021). We anticipated gill lice occupancy would be negatively associated with brown trout biomass given that S. edwardsii is not known to parasitize brown trout (Mitro, 2016), but this effect was of similar magnitude to the effect of brook trout biomass.…”
Section: Predicting Occupancy With Fish Metabarcoding and Conventiona...mentioning
confidence: 83%
See 4 more Smart Citations
“…edwardsii may be dependent on host density, as has been noted for other Salvelinus fishes (Hasegawa & Koizumi, 2021). We anticipated gill lice occupancy would be negatively associated with brown trout biomass given that S. edwardsii is not known to parasitize brown trout (Mitro, 2016), but this effect was of similar magnitude to the effect of brook trout biomass.…”
Section: Predicting Occupancy With Fish Metabarcoding and Conventiona...mentioning
confidence: 83%
“…Although we did not detect gill lice DNA in these disjunct streams during our study, a brook trout from this stream cluster captured via electrofishing was reported to have a single gill louse the year after our study (Katz et al., 2023). Future work considering how temporal and environmental variation affect trout and gill lice occupancy could help clarify distributional differences among these species and potentially aid in detecting early gill lice infestations (Hasegawa & Koizumi, 2021; Wilcox et al., 2018). For example, sampling across multiple seasons may reveal differing relationships for DNA occupancy of focal taxa and prey diversity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations